ANALISIS STRATEGI PEMASARAAN MARMER - Arief Nugroho Wibowo (Universitas Indraprasta PGRI, 2016)
Marble is a finishing material which is relatively expensive compared to ceramic or the like, marble is a supporting products or components that are very closely tied to the construction sector in Indonesia in general and in particular on projects in housing, buildings and other buildings. Courage firm in hopes of competing with firm steps in line with the wishes and expectations of consumers as well as other stekholder. Leadership of a company is not a guarantee, produkdan certain brands will not always stable, many newcomers trying to destabilize the position with the finesse of a strategy that diverse. This shows that the business is a war, so we need to do pendekataan strategy for Integration managed to outperform other product strategy in the competition, which is a product that is superior and high quality. Basically, the principle of the strategies in the face of the problems that often arise in everyday business activities, it is a more practical method in the decision-making. Consumers are very subjective assessment of the quality of service so it is very difficult to evaluate than product quality, service quality can be evaluated not only on service alone but in the service process, so having a relative criteria. Several driving factors to achieve a success as follows: Must have a clear purpose or direction, can recognize the environment as well as possible, and be familiar with and be able to measure yourself in depth, consistency and commitment. This study describes the strategies used by PT.CITATAH as marble industry in improving its sales, it encourages writers in researching, menkaji and analyze to what extent the application and the suitability of the strategies used, and determine its market share, so it can be determined the direction and strategy and the result. Keyword: Marketing Strategy, Marble